Application of Signs and Symbols of Diversity and Pancasila Values in the School Ecosystem and Learning Process at SMA Negeri 11 Palembang: Application of Signs and Symbols of Diversity and Pancasila Values in the School Ecosystem and Learning Process at SMA Negeri 11 Palembang - Yuliana, Yuliana (Experimental Student Experiences, 2022)
This study aims to find out how the application of signs and symbols that contain the values ​​of Diversity in Diversity and Pancasila as Indonesian human identities applied at SMA Negeri 11 Palembang. This research is a qualitative research using observation method. Data collection techniques were used by means of interviews with the schools involved, direct observation and distributing Google-Forms that students had to fill out. Research results show that SMA Negeri 11 Palembang has implemented the values ​​of diversity and Pancasila well, which can be seen from the absence of discrimination between educators and students as well as students and other students as well as mutual respect and mutual respect tolerance between religions, races, ethnicities, cultures.